PENGENALAN DAUR ULANG SAMPAH MELALUI PERMAINAN EDUKATIF DI TK ISLAM EL-SYIFA CIGANJUR JAKARTA SELATAN - Dadan Sundara; Albert P Akbar Putra; Ulistina Ramdani; Anissa Aulia (Jurnal Pengabdian Teratai, 2026)
Urban waste problems remain a serious environmental issue in Indonesia, particularly in densely populated areas such as South Jakarta. One of the main causes is the lack of early environmental education, especially regarding waste sorting and recycling. This community service program aimed to introduce basic concepts of waste management and recycling to early childhood students at TK Islam El-Syifa Ciganjur through play-based learning methods. The activities included watching educational videos, singing environmental songs, waste sorting games, and creating simple crafts from recycled plastic bottle caps. The evaluation was conducted through observation, activity sheets, and simple post-tests. The results showed that 93.8% of students were able to correctly distinguish between organic and inorganic waste after the program. Students also demonstrated high participation and creativity throughout the activities. These findings indicate that play-based learning is an effective approach to instilling environmental awareness and positive waste management behavior in early childhood education.